2023
DOI: 10.5705/ss.202020.0358
|View full text |Cite
|
Sign up to set email alerts
|

Robust Inference for Partially Observed Functional Response Data

Abstract: Irregular functional data in which densely sampled curves are observed over different ranges pose a challenge for modeling and inference, and sensitivity to outlier curves is a concern in applications. Motivated by applications in quantitative ultrasound signal analysis, this paper investigates a class of robust M-estimators for partially observed functional data including functional location and quantile estimators. Consistency of the estimators is established under general conditions on the partial observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Instead, we can calculate the n × L proxy matrix, denoted as Φ Y , by computing basis coefficients for ψ l (t) on the expansion of demeaned Y i (t), i.e., I {Y i (t) − μ(t)}ψ l (t)dt, where μ(t) = n −1 n i=1 Y i (t). We note that nonparametric methods, such as local or spline smoothing regression models, or robust mean estimates under functional M-estimator (Park et al, 2022), can be adopted in estimating µ(t). When considering functional data collected over individual-specific domains, Y i (t), for t ∈ I i ⊂ I, the basis coefficients are calculated by Ii {Y i (t) − μ(t)}ψ l (t)dt, for t ∈ I i .…”
Section: Data-adaptive Matrix Decomposition With L 1 Regularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, we can calculate the n × L proxy matrix, denoted as Φ Y , by computing basis coefficients for ψ l (t) on the expansion of demeaned Y i (t), i.e., I {Y i (t) − μ(t)}ψ l (t)dt, where μ(t) = n −1 n i=1 Y i (t). We note that nonparametric methods, such as local or spline smoothing regression models, or robust mean estimates under functional M-estimator (Park et al, 2022), can be adopted in estimating µ(t). When considering functional data collected over individual-specific domains, Y i (t), for t ∈ I i ⊂ I, the basis coefficients are calculated by Ii {Y i (t) − μ(t)}ψ l (t)dt, for t ∈ I i .…”
Section: Data-adaptive Matrix Decomposition With L 1 Regularizationmentioning
confidence: 99%
“…As the first step, we estimate the mean function by calculating the Hubertype location estimator Park et al (2022), a class of functional M-estimator applicable to the data containing atypically behaved trajectories with missing segments. We then implement the proposed algorithm to demeaned trajectories by employing 51 Fourier basis functions for orthonormal basis functions ψ l (t) with q = 10.…”
Section: Advanced Metering Infrastructure Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent works have begun addressing the estimation of covariance functions for short functional segments observed at sparse and irregular grid points, called functional snippets (Lin and Wang, 2020;Lin et al, 2021) or for fragmented functional data observed on small subintervals (Delaigle et al, 2020). For densely observed partial data, existing studies have focused on estimating the unobserved part of curves (Kneip and Liebl, 2020;Kraus and Stefanucci, 2020), prediction (Goldberg et al, 2014), classification (Kraus and Stefanucci, 2018;Park and Simpson, 2019), functional regression (Gellar et al, 2014), and inferences (Kraus, 2019;Park et al, 2022).…”
Section: Introductionmentioning
confidence: 99%